Respuesta :
Answer:
x = -3
Topics are listed below.
Step-by-step explanation:
Topics of this question include:
- Solving equations with variables
- Distributive property
- Balancing Equations
Solve:
- 9 - 4(5 - x) = 3(x - 1) -2
- 9 - 20 + x = 3x - 3 - 2
- -11 + x = 3x - 5
- -2x = 6
- x = -3
-Chetan K
Answer:
The value of x is 6.
Step-by-step explanation:
Concept :
Here, we will use the below following steps to find a solution using the transposition method:
- Step 1 :- we will Identify the variables and constants in the given simple equation.
- Step 2 :- then we Simplify the equation in LHS and RHS.
- Step 3 :- Transpose or shift the term on the other side to solve the equation further simplest.
- Step 4 :- Simplify the equation using arithmetic operation as required that is mentioned in rule 1 or rule 2 of linear equations.
- Step 5 :- Then the result will be the solution for the given linear equation.
[tex]\begin{gathered}\end{gathered}[/tex]
Finding the value of x.
[tex]\begin{gathered}\quad\implies{\tt{9 - 4(5 - x)=3(x - 1) - 2 }}\\\\\quad\implies{\tt{9 - (4 \times 5 - 4\times x)=(3 \times x - 3 \times 1) - 2}}\\\\\quad\implies{\tt{9 - (20 - 4x)=(3x - 3) - 2}}\\\\\quad\implies{\tt{9 - 20- 4x=3x - 3- 2}} \\\\\quad\implies{\tt{- 11 - 4x=3x - 5}}\\\\\implies{\tt{- 4x + 3x = - 11 + 5}} \\ \\\implies{\tt{-x = - 6}}\\\\ \implies{\tt{ \cancel{-}\: x = \cancel{-} 6}}\\\\\quad\implies{\tt{x = 6}}\end{gathered}[/tex]
Hence, The value of x is 6.
[tex]\rule{300}{2.5}[/tex]